Quantification of Canine Dental Plaque Using Quantitative Light-Induced Fluorescence. (March 2016) - Wallis, Corrin; Gill, Yadvinder; Colyer, Alison; Davis, Ian; Allsopp, Judi; Komarov, Gleb; Higham, Susan; Harris, Stephen
The aim of this work was to evaluate Quantitative Light-induced Fluorescence (QLF TM ) as an alternative to the established Logan and Boyce method for determining plaque coverage of dogs' teeth. In a series of studies in conscious and anesthetized dogs, QLF showed good intra-photographer repeatability (coefficient of variation [CV] of 7.5% for undisclosed teeth) and inter-photographer reproducibility (CV of 3.2% for undisclosed teeth and 8.5% for disclosed teeth). The QLF software accurately identifies areas of plaque as demonstrated by comparison to the variability of 5 human scorers, manually marking plaque on QLF-acquired images ( P = 0.1). There was good agreement with the modified Logan and Boyce method in the percentage reduction in plaque accumulation measured when dogs were fed an oral care chew versus no chew. To see a 15% difference in plaque accumulation, which is considered sufficient by the Veterinary Oral Health Council to differentiate between 2 treatments, a retrospective power analysis (90%) of the data established that only 7 dogs would be required, compared to 19 dogs for the modified Logan and Boyce method. QLF is a reliable method for measuring dental plaque in dogs with the added advantage that it is not subjective and requires fewer animals.